On the Kinematics and Actuation of Dynamic Sunscreens With Tensegrity Architecture - Babilio, Enrico; Miranda, Raffaele; Fraternali, Fernando (Frontiers in Materials, 2019)
This paper presents a mechanical study on the use of tensegrity lattices for the design of energy efficient sunscreens inspired by the dynamic solar façades of the Al Bahar Towers in Abu Dhabi. The analyzed screens tassellate origami modules formed by 12-bar and 3-string tensegrity systems. The actuation of each module is controlled through the stretching of the perimeter strings, which form macro-triangles moving parallel to the building, while all the bars and the fabric mesh infills form micro-triangles that are allowed to move rigidly in space. We develop an analytic formulation of the deformation mapping associated with such an actuation motion, which gives rise to a morphing-type behavior. We also estimate the energy that is needed to activate the analyzed shading system, and establish a comparison between its weight and that of the original screens of the Al Bahar Towers. The proposed tensegrity design concept leads to realize shading screens that are markedly lightweight, work on very low energy consumption, and can be usefully employed to harvest solar and wind energies.